Effects of suckling on dairy cows reproduction: a review - Ferreira, Ademir de Moraes (Pesquisa Agropecuaria Brasileira, 1992)
The long post-partum anestrus is one of the main causes for the long days open, and consequently, the low reproductive efficiency in bovine herd in Brazil. Suckling effect is listed as able to influence the period between calving and the first estrus, in both dairy and beef cattle. This review shows several research results about the effects of the suckling on reproduction, and describes several routes in which suckling the udder by calf could affect ovary activity. The main objective of this review is to provide a background to improve knowledge in the area and to attract increased investigation for the especific mechanism by which the reproductive function is affected by suckling.